The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/aos.12121
|View full text |Cite
|
Sign up to set email alerts
|

Senile retinoschisis versus retinal detachment, the additional value of peripheral retinal OCT scans (SL SCAN‐1, Topcon)

Abstract: Key words: integrated SD-OCT into a slit lamp -optical coherence tomography -retinal detachment -senile retinoschisis -SL SCAN-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Likewise, our data for age and refraction, which showed a slight accumulation of emmetropia to hyperopia in RS cases, were similar to population‐based studies (Byer ; Stehouwer et al. ). Further, the incidence rate of bilateral appearance of RS differs in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, our data for age and refraction, which showed a slight accumulation of emmetropia to hyperopia in RS cases, were similar to population‐based studies (Byer ; Stehouwer et al. ). Further, the incidence rate of bilateral appearance of RS differs in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Stehouwer et al. () also found cystic alterations without further retinal splitting, which they described as common finding in long‐standing RD.…”
Section: Discussionmentioning
confidence: 87%
“…The OCT of the posterior edge showing a complete separation of the neurosensory retina from the RPE can also be seen in retinoschisis associated with frank rhegmatogenous retinal detachment and in schisis-detachment 17 18…”
Section: Introductionmentioning
confidence: 91%
“…OCT of retinal periphery has been previously reported and shows retinoschisis as a split in the neurosensory retina: the outer leaf is a distinct separate layer lying in apposition to the hyper-reflective band of the RPE8 16 17 Retinal detachment, on the other hand, is seen as a complete detachment of the neurosensory retina from the RPE surface8 16 17 However, making the diagnosis based on OCT imaging of the posterior edge can be too simplistic. The OCT of the posterior edge showing a complete separation of the neurosensory retina from the RPE can also be seen in retinoschisis associated with frank rhegmatogenous retinal detachment and in schisis-detachment 17 18…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that shorter duration of macular detachment is associated with better visual acuity outcomes 2. Recent studies have reported the use of spectral-domain optical coherence tomography (SD-OCT) in the evaluation and follow-up of patients with retinal detachment and retinoschisis 3,4. In the current study, four patients with macula-off retinal detachment are reported that underwent surgical repair at various time points after symptom onset with preoperative and postoperative clinical and anatomic correlation using SD-OCT.…”
Section: Introductionmentioning
confidence: 99%